2008
DOI: 10.1002/ange.200803242
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Component Liquid Crystals as Chiral Reaction Media: Highly Enantioselective Photodimerization of an Anthracene Derivative Driven by the Ordered Microenvironment

Abstract: Maßgeschneiderte Umgebung: Innerhalb einer flüssigkristallinen Matrix aus einem chiralen amphiphilen Aminoalkohol findet die Photodimerisierung einer Anthracencarbonsäure mit hoher Wahrscheinlichkeit sowie hervorragenden Regio‐, Diastereo‐ und Enantioselektivitäten statt (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In fact, we have recently reported that the salts of trisA C H T U N G T R E N N U N G (alkyloxy)benzoic acid derivatives with various amino alcohols have a general tendency to exhibit thermotropic LC phases. [12,13,16] In this work, (1R,2S)-norephedrine (guest amine; G RS ) was selected, because an abundant amount of data have been accumulated by our group on the structure and properties of the LC salts of G RS with amphiphilic carboxylic acids. In addition, easy access to its antipode ((1S,2R)-norephedrine, G SR ) and diastereoisomers ((1R,2R)-and (1S,2S)-pseudonorephedrine, G RR and G SS ) would allow us to investigate the chirality recognition ability of the resultant polymers.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, we have recently reported that the salts of trisA C H T U N G T R E N N U N G (alkyloxy)benzoic acid derivatives with various amino alcohols have a general tendency to exhibit thermotropic LC phases. [12,13,16] In this work, (1R,2S)-norephedrine (guest amine; G RS ) was selected, because an abundant amount of data have been accumulated by our group on the structure and properties of the LC salts of G RS with amphiphilic carboxylic acids. In addition, easy access to its antipode ((1S,2R)-norephedrine, G SR ) and diastereoisomers ((1R,2R)-and (1S,2S)-pseudonorephedrine, G RR and G SS ) would allow us to investigate the chirality recognition ability of the resultant polymers.…”
Section: Resultsmentioning
confidence: 99%
“…(iii) Owing to the availability of various photoreactive carboxylic acids, as well as the noncovalency of interaction between the two components, such 2-amino alcohol units would offer a special environment to various substrates/reactions. As the first successful example of this approach, we recently reported that the photodimerization of 2-anthracenecarboxilic acids generated a satisfactory yield with unprecedented high enantioselectivity, by using a two component LC matrix as the reaction medium ( Figure 11 ) [ 19 , 20 ].…”
Section: Tailored Reaction Mediamentioning
confidence: 99%
“…Therefore, in situ reactions in LCs would lead to a new type of tailored micro-environment, which may realize highly efficient/selective molecular recognitions and chemical reactions. This review summarizes our recent effort to develop a new class of micro-environment based on the in situ reactions in LCs [ 16 , 17 , 18 , 19 , 20 ]. In relation to our studies, we also provide an overview of notable works related to LC-template reactions, from historically important reports to recent trends.…”
Section: Introductionmentioning
confidence: 99%
“…In a more positive light, however, one can consider this complexity to be a probe to explore and monitor the molecular phenomena involved in the stereochemical course of a process, especially in terms of molecular arrangement, fine‐tuned by noncovalent interactions that participate in supramolecular chirogenesis. Substrate preorientation prior to photoreaction, governed by means of the supramolecular interactions, has recently been exploited to achieve highly regio‐ and enantioselective photodimerization of 2Ac in solution,3 in the solid state4 by using the inherently chiral cavity of γ‐cyclodextrin derivatives, and in two‐component liquid crystalline medium as well 5. However, all are sensitive to the design or fine‐tuning of the appropriate host molecules.…”
Section: Introductionmentioning
confidence: 99%